The Outsiders - Hinton S. E (New York Viking press, 1995)
The struggle of three brothersto stay together after their pareants death and their quest for identity among the conflicting values of thire adolescent society
American CORNER
11
Keywords: Family life -- ficition; Gangs -- ficition